A Catalytic Mechanism for d-Tyr-tRNA(Tyr) Deacylase Based on the Crystal Structure of Hemophilus influenzae HI0670 - Lim, Kap (2003)
d-Tyr-tRNA(Tyr) deacylase is an editing enzyme that removes d-tyrosine and other d-amino acids from charged tRNAs, thereby preventing incorrect incorporation of d-amino acids into proteins. A model for the catalytic mechanism of this enzyme is proposed based on the crystal structure of the enzyme from Haemophilus influenzae determined at a 1.64-Å resolution. Structural comparison of this dimeric enzyme with the very similar structure of the enzyme from Escherichia coli together with sequence analyses indicate that the active site is located in the dimer interface within a depression that includes an invariant threonine residue, Thr-80. The active site contains an oxyanion hole formed by the main chain nitrogen atoms of Thr-80 and Phe-79 and the side chain amide group of the invariant Gln-78. The Michaelis complex between the enzyme and d-Tyr-tRNA was modeled assuming a nucleophilic attack on the carbonyl carbon of d-Tyr by the Thr-80 O(γ) atom and a role for the oxyanion hole in stabilizing the negatively charged tetrahedral transition states. The model is consistent with all of the available data on substrate specificity. Based on this model, we propose a substrate-assisted acylation/deacylation-catalytic mechanism in which the amino group of the d-Tyr is deprotonated and serves as the general base.